Non-contiguous finished genome sequence and description of Bacillus massilioanorexius sp. nov. Issue 3 (May 2013) - Mishra, Ajay; Pfleiderer, Anne; Lagier, Jean-Christophe; Robert, Catherine; Raoult, Didier; Fournier, Pierre-Edouard
Abstract Bacillus massilioanorexius strain AP8T sp. nov. is the type strain ofB. massilioanorexius sp. nov., a new species within the genusBacillus . This strain, whose genome is described here, was isolated from the fecal flora of a 21-year-old Caucasian French female suffering from a severe form of anorexia nervosa since the age of 12 years.B. massilioanorexius is a Gram-positive aerobic bacillus. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 4, 616, 135 bp long genome (one chromosome but no plasmid) contains 4, 432 protein-coding and 87 RNA genes, including 8 rRNA genes.